Haemophagocytic lymphohistiocytosis associated with coccidiomycosis - Ramsi, Musaab (BMJ Publishing Group, 2014)
Haemophagocytic lymphohistiocytosis (HLH) is a rapidly fatal disease caused by dysregulated histiocytes leading to an excessive inflammatory reaction. While genetic forms of HLH exist, the most common form is acquired, frequently associated with infection. Here we report the first case of HLH associated with a coccidiomycosis infection. This patient is a 13-year-old previously healthy boy who presented with a flu-like illness, which rapidly progressed to refractory shock, severe ARDS, multiorgan failure and death despite maximal medical therapy, including broad-spectrum antibiotics to treat well-established causes of acquired HLH. Autopsy findings revealed the diagnosis of HLH in the setting of pulmonary coccidiomycosis. Antifungal therapy should be considered in cases of acquired HLH when the underlying aetiology is not clear.